Prinsip Komunikasi Dakwah dalam Al-Qur’an menurut Fakhruddin Ar-Razi: مبادئ الحوار الدعوي في القرآن الكريم عند فخر الدين الرازي - Ihwan Agustono; Harirotuz Zahrok, Ummu (Institut Muslim Cendekia, 2026)
Advances in information technology have brought about significant changes in the patterns of dialogue within society and raised various ethical issues, such as hate speech, verbal abuse, and the erosion of meaning in the digital space. This situation underscores the importance of ethical and spiritual values in the practice of dialogue, particularly in da’wah dialogue. The Qur’an, as the primary source of Islamic teachings, contains principles of ethical dialogue formulated by classical exegetes, and the selection of Fakhruddin Ar-Razi’s exegesis in this study is based on several scholarly considerations. Ar-Razi is known for the depth of his rhetorical and rational analysis of the Qur’anic text, and his exegetical methodology is characterized by the integration of theological debate and philosophical analysis in understanding the Qur’anic discourse. This study aims to examine the principles of da’wah dialogue in the Qur’an according to Fakhruddin Ar-Razi, with a focus on the exegesis of verses containing the concept of “qawl.” The concept of “qawlan” in this study does not refer to speech in an absolute sense, but rather to Qur’anic expressions that appear in the form of “qawlan” accompanied by ethical or communicative descriptions, such as “qawlan sadida,” “qawlan layyina,” and “qawlan karima.” These expressions represent the Qur’anic value system that governs the ethics of discourse and dialogue in Islam. An analysis of their meanings and potential applications in the context of contemporary dialogue. The method used is qualitative research based on a literature review with a thematic interpretation approach. The research stages include the collection of Qur’anic verses related to the concept of “qawlan,” linguistic and contextual analysis of these verses, as well as a critical reading of the logic and exegesis of Fakhruddin Ar-Razi in the book Mafatih al-Ghaib. The research findings indicate that, according to Ar-Razi, da’wah dialogue must combine rational arguments with the ethics of speech. Principles of speech such as familiar speech, easily understandable speech, and eloquent speech lead this study to focus on three primary models: appropriate speech, gentle speech, and noble speech. As a framework for Qur’anic dialogue, this is because these three models represent central dimensions in da’wah dialogue, namely the dimension of epistemological honesty, the dimension of psychological gentleness, and the dimension of relational ethics. The uniqueness of this research lies in its connection to issues of dialogue in the digital space; however, the mechanism of this connection has not been clearly explained, which impacts the strengthening of ethical and contextual models of da’wah dialogue in the modern era.